2021
DOI: 10.3390/languages6010013
|View full text |Cite
|
Sign up to set email alerts
|

Keeping a Critical Eye on Majority Language Influence: The Case of Uptalk in Heritage Spanish

Abstract: The goal of this study is to highlight the importance of taking into account variations in monolingual grammars before discussing majority language influence as a possible source of heritage speakers’ divergent grammars. In this study, we examine the production of uptalk in Spanish by heritage speakers of Mexican Spanish in Southern California. Uptalk (i.e., rising intonation contour at the end of a non-question utterance) is frequently associated with California English. Thus, heritage speakers’ use of uptalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…If we were to assume this perspective, in large part due to speech style similarities, we could posit that the falling pitch accent (H+L*) was already in the speech of our G1 speakers when they arrived in Sweden, was actually supported by contact with the similar, falling small tone accent 1 in Stockholm Swedish, and was then transmitted to G2 due to frequent interactions in Spanish and the density of the Chilean diaspora in the Stockholm area. This discussion shows some alignment with work on uptalk by Kim (2023) and Kim and Repiso-Puigdelliura (2021), where it was uncovered that while this feature is associated with Californians, it was also exhibited in monolingual speakers of Mexican Spanish but implemented in different ways. Through more detailed phonetic analyses and data sets of comparison, we can further elucidate the nature of the falling movements in question.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…If we were to assume this perspective, in large part due to speech style similarities, we could posit that the falling pitch accent (H+L*) was already in the speech of our G1 speakers when they arrived in Sweden, was actually supported by contact with the similar, falling small tone accent 1 in Stockholm Swedish, and was then transmitted to G2 due to frequent interactions in Spanish and the density of the Chilean diaspora in the Stockholm area. This discussion shows some alignment with work on uptalk by Kim (2023) and Kim and Repiso-Puigdelliura (2021), where it was uncovered that while this feature is associated with Californians, it was also exhibited in monolingual speakers of Mexican Spanish but implemented in different ways. Through more detailed phonetic analyses and data sets of comparison, we can further elucidate the nature of the falling movements in question.…”
Section: Discussionsupporting
confidence: 56%
“…For both categories of focus, the former exhibited a preference for stress shift, while also using p-movement and simple clefts to a lesser degree, whereas the latter avoided stress shift and distinguished productions based on focus type, employing pseudo-clefts and p-movement for narrow information focus and simple clefts and focus fronting for contrastive focus. Finally, the last pair of studies to which we should draw attention, by Kim and Repiso-Puigdelliura (2021) and Kim (2023), deals with uptalk in heritage speakers of Mexican Spanish in California. While this feature is commonly tied to California English, the former study actually shows that it is present in the Spanish of both heritage speakers and monolingual speakers of Mexican Spanish, but is manifested in different ways (pointing to majority language influence in the former group), revealing that understanding the origin of intonational phenomena attested in heritage speech requires delving deeper into comparison groups rather than defaulting to majority language influence alone.…”
Section: Relevant Previous Work On Heritage Spanish Intonationmentioning
confidence: 99%
“…Finally, when placing our f0 range results beside previous studies involving this variable in Spanish and English, such as those of Estebas-Vilaplana (2014) and Harris et al (2015), we note that while f0 excursions and range tend to be wider in English, our HSS data reveal the opposite pattern. 4 Upon returning to the notion of English communication of sarcasm vs. sincerity as a baseline in our participants and adding the comments on sound system hybridity in heritage speakers by authors such as Kim (2019) and Kim and Repiso-Puigdelliura (2021), we suggest that our HSS start with a wider range in English than what we would expect in the Spanish of a Spanishdominant speaker, and then filter their Spanish productions through the English strategies, which cause them to draw upon the English feature of an increased f0 range, rather than suppressing it toward what we would expect in Spanish. By adopting English's range trend, the Spanish range data is thus boosted relative to those of English.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when compared to monolingual Spanish speakers, Chicano HSS, as seen in Harris et al (2015), convey new information through f0 manipulation rather than word order, which is typical of monolingual varieties of English, suggesting contact influence. Contributing to the body of research on language influence, a recent study on uptalk in HSS by Kim and Repiso-Puigdelliura (2021) compares the intonational contours of uptalk in heritage speakers of Mexican Spanish in Southern California and monolingual speakers of Mexican Spanish. Uptalk in HSS is often attributed to influence from English; however, the authors have found evidence of uptalk in monolingual Mexican Spanish as well.…”
Section: Spanish Heritage Speaker Prosodymentioning
confidence: 99%